Gambaran Pengetahuan Ibu Tentang Penyakit Gigi Dan Mulut Anak di Masa Pandemi Covid-19 : Kajian pada Ibu Siswa-siswi SDIT Buah Hati (Laporan Penelitian) - Elvinadaya Ariefa Putri; Sri Ratna Laksmiastuti (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Background: Children’s oral health is very important. Oral health is essential to build body immune system specially in Covid-19 pandemic. The parents should pay attention for this matter. Mother’s knowledge and awareness about children's oral health will affect their attitudes and behavior. Based on literature, there are a significant correlation between mother’s oral health status and their children. The high prevalence of oral disease can be caused by lack of mother’s knowledge and awareness. Objective: To asses maternal knowledge about oral diseases during the Covid-19 pandemic at SDIT Buah Hati. Methods: A descriptive observational study with a cross-sectional design was conducted on 96 mothers.The data were obtained using google form questionnaire and presented in the form of frequency distribution tables. The reliability and validity test is based on Cronbach’s Alpha and correlation’s coefficient value. Results: Mothers knowledge about oral diseases in children during the Covid-19 pandemic were 28% in good categories, 72% in moderate category and 0% in deficient category. Conclusion: Most of mothers have moderate knowledge about oral diseases in children.